Strategies and Models of Character Education Based on Religious Values in the Era of Globalized Education - Bahiyah, Umamatul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze strategies and develop an effective model of character education based on religious values in response to the challenges posed by globalization. While globalization positively impacts technological advancement and information accessibility, it also triggers moral crises, value disorientation, and character degradation, particularly among the younger generation. This research adopts a qualitative approach using the literature review method, examining various sources related to character education and religious values within global education. The findings indicate that effective character education strategies must integrate spiritual, moral, and cognitive dimensions into formal and non-formal curricula through contextual, participatory, and sustainable approaches. The developed character education model emphasizes inclusivity, contextual relevance, and the involvement of all stakeholders, including teachers, school principals, families, and communities. Religious values such as honesty, responsibility, and tolerance are the foundation for shaping students' character. This study recommends policy synergy between central and local governments, continuous teacher training, and the utilization of digital technology as a medium for teaching religious values. Through this approach, character education can foster a generation with integrity that is resilient against the negative influences of globalization.